Preparation And Evaluation Of Hydrogel From Super Red Dragon Fruit Skin Extract (Selenicereus costaricensis) - Setiawan, Dwi; Yesti, Yulia; Rahmadasmi, Nola; Fitriani, Oryza Sativa; Andika, Miming; Hasanah, Rizqa; .AH, Ahdi Dinil Haq; Wulandari, Desti; Putri, Nurdina (Poltekkes Kemenkes Riau, 2024)
Dragon skin is a waste that is rarely used and often discarded. The dragonfruit skin has antioxidant activity related to the anthocyanin content that protects the skin from oxidation damage to prevent premature aging. This study introduces a new approach to utilizing super red dragon fruit skin waste often thrown away, by formulating it into a hydrogel preparation with potential as a cosmetic product. An experimentally used method with a true-experimental design. There are 7 formulas, F1 (base), F2, F3, and F4 (with ultrasonic extract 1%, 2%, 3.). The evaluations included organoleptic tests, homogeneity tests, viscosity testing, pH tests, swelling ratio, freeze and thaw. The results of this study show that super red dragonfruit leather extracts can be formed in hydrogel preparations and have good physical quality properties.